Analysis of the Implementation of E-BPHTB Online and Its Impact on Local Tax Revenue and Public Compliance in DKI Jakarta - Salsa Fadhilah; Arfah Habib Saragih; Adang Hendrawan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2025)
The DKI Jakarta government has implemented tax reforms by introducing e-BPHTB. The e-BPHTB aims to simplify the process for the public to fulfill their BPHTB tax obligations. This study was conducted to analyze the implementation of e-BPHTB online and its impact on local tax revenue and public compliance in DKI Jakarta province, to identify the driving and inhibiting factors in the implementation of e-BPHTB online, and to evaluate the system’s effectiveness. The study employs a qualitative approach through literature review and field research. The results indicate that the supervision policy of BPHTB is functioning well by providing oversight to taxpayers through cooperation with relevant parties. However, the implementation of e-BPHTB has not significantly impacted local tax revenue and public compliance due to the limited number of taxpayers utilizing the system and the inefficiency of the approval system. Public trust is considered positive due to the facilities provided by the government, including e-BPHTB. The driving factors for implementing e-BPHTB online are threefold: advancements in technology, the perceived ease experienced by taxpayers and tax authorities, and the COVID-19 pandemic. The inhibiting factors include limited public familiarity with technology, the inefficiency of the approval system due to the need for human resources, and the lack of human resource quality. The success rate of e-BPHTB implementation is evaluated based on two factors: the limited competence of human resources due to the absence of training for tax officers, and the need for improvement in the approval system application.